DISSOCIATIVE IDENTITY DISORDER: A NARRATIVE REVIEW - dos Santos , Felippo Ataide; Sampaio, Júlia Inácio Pedro; Junior, Adoniram Nunes Pereira; Lôbo, Ana Luiza Silva (Seven Editora, 2024)
Dissociative Identity Disorder (DID), formerly known as Multiple Personality Disorder, is a complex psychiatric condition characterized by the presence of two or more distinct identities or personality states that alternate in controlling an individual's behavior. DOI:https://doi.org/10.56238/sevened2024.029-039